The economic impact of streaming beyond GDP - Harald Edquist; Peter Goodridge; Jonathan Haskel (International Telecommunications Society (ITS), 2020)
This paper finds that the shift from buying music as a physical product towards subscribing to music services implies a decrease of 85 percent in the price paid per song. We estimate that in 2019 the global quality adjusted value from streamed music was 76 billion compared to current revenues of 11.4 billion. Thus, the shift from consuming music in physical form towards subscribing to music services creates an enormous consumer surplus that is not recorded in GDP.
Keywords: O31; O33; O34; 330; Streaming; price index; mobile broadband